2016
DOI: 10.17957/tpmj/16.3226
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Albino Rats; Blood Glucose, Superoxide Dismutase and Glutathione Peroxidase in Cinnamon Cassia Treated

Abstract: The present study evaluated the blood glucose, superoxide dismutase (SOD) and glutathione peroxidase (GPX) in Cinnamon cassia bark extract (CCBE) treated alloxan-induced diabetic albino rats. Study Design: Experimental study. Setting: Animal house of Al-Tibri Medical College, Karachi was selected for conducting the present study. Period: January 2014 to December 2014. Methodology: A sample of twenty rats was randomly divided into 4 groups. Rats were grouped as A1 (n=5)-Negative control, A2 (n=5)-Positive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Administration of cinnamon powder at a dose of 75 mg/kg for 30 days significantly increased serum levels of SOD, CAT, GPx, and decreased MDA levels in all diabetic groups receiving cinnamon [98]. These findings were consistent with two other studies, which showed that cinnamon extract administration increased SOD and GPx enzyme activity, with the most significant effect observed at a dose of 200 mg/kg [99,100].…”
Section: The Antioxidative Potential Of Ginger and Cinnamon: Evidence...supporting
confidence: 88%
“…Administration of cinnamon powder at a dose of 75 mg/kg for 30 days significantly increased serum levels of SOD, CAT, GPx, and decreased MDA levels in all diabetic groups receiving cinnamon [98]. These findings were consistent with two other studies, which showed that cinnamon extract administration increased SOD and GPx enzyme activity, with the most significant effect observed at a dose of 200 mg/kg [99,100].…”
Section: The Antioxidative Potential Of Ginger and Cinnamon: Evidence...supporting
confidence: 88%